Polymorphic variants of the dopamine receptor gene DRD2 (rs6277, rs1800497) in adolescents with problematic video game use - S. Yu. Tereshchenko; K. V. Afonicheva; I. V. Marchenko; M. V. Shubina; M. V. Smolnikova (Вавиловский журнал генетики и селекции)
Problematic video games use, as a specific form of problematic Internet use, is widespread among adolescents and can have negative effects on their mental and somatic well-being. An increasing incidence of addictive video gaming, as well as the overuse of the Internet, among the young population makes the current study of susceptibility factors, including the genetic component, relevant. There has been a number of investigations related to the involvement of gene variants of the neurotransmitter system in the development of Internet addiction, with the results being different for various ethnic groups. The dopamine type 2 receptor gene (DRD2) is one of the candidate genes for susceptibility to video game addiction. The aim of the work was to study polymorphic variants of the dopamine receptor gene DRD2 (rs6277, rs1800497) in Russian adolescents with problematic use of computer video games. A sampling of 407 adolescents aged 14.1±1.8 years was tested, of which 56 (13.8 %) were identified as having problems with the pathological use of video games use based on the GASA scale results. Boys in the sample proved to be addicted to video games more than girls (p = 0.041). As a result of comparing the allele frequency of DRD2 (rs6277), a tendency to a higher frequency of the minor allele T was revealed in the group of adolescents with problematic video game use compared with adolescents without problematic video game use (i. e. 0.563 and 0.466, respectively, p = 0.06). When using the dominant inheritance model, it was revealed that adolescents with problematic use of video games were statistically significantly more likely to carry the T (CT+TT) allele (p = 0.04, OR = 2.14, CI = 1.01–4.53). The T allele DRD2 (rs6277) is associated with low expression of the dopamine receptor D2 and leads to decreasing the density and affinity of extrastriatal dopamine type 2 receptors, which is associated with impaired social communication as well. We suggest that the presence of CT and TT genotypes of rs6277 DRD2 may be a potential risk factor for developing problematic video game use in adolescents.